The role of material and technical support in industrial construction - Prykhodko, D.; Ivanyna, O.; Naumenko, K.; Herasymchuk, Y. (Ways to Improve Construction Efficiency, 2024)
Material and technical support in industrial construction serves as the foundation for stability, continuity, and efficiency of production processes. The construction industry, as one of the most resource-intensive sectors of the economy, requires systematic management of material, equipment, and technical resource flows. The conditions of modern industrial development necessitate the formation of new approaches to organizing logistics processes that integrate information technologies, analytical systems, and demand forecasting methods. Poor organization in the supply sector often leads to project delays, resource overruns, decreased labor productivity, and increased construction costs. Optimization of material and technical support is a multifaceted task that encompasses supplier selection, inventory management, transportation logistics, quality control, and the use of digital tools to improve transparency and manageability of processes. An important component in this context is the implementation of ERP systems and cloud platforms, which make it possible to integrate planning, procurement, accounting, and performance monitoring into a unified information base. The use of such tools helps reduce transaction costs, minimize the risks of shortages or surpluses of materials, and increase the accuracy of managerial decisions. In industrial construction, timeliness and reliability of supplies play a crucial role. Large-scale projects require a clearly structured supply system that takes into account the specifics of technological processes and enables coordination of activities among all project participants. Modern digital solutions provide opportunities for scenario modeling, risk forecasting, and rapid response to changes in the external environment. Thus, material and technical support emerges not only as a functional element of construction but also as a strategic factor in the competitiveness of enterprises. Rational organization of this process allows not only for improving economic indicators but also for ensuring the quality and reliability of industrial facilities.